Strengthening Organic Rice–Fish Farming Through Participatory Focus Group Discussions and International Collaboration in North Sumatra, Indonesia - Hotnida Sinaga; Meutia Nauly; Sri Fajar Ayu; Destanul Aulia; Salmiah Salmiah; Patricia Srisere Ikaria Situmorang (RIRAI Publisher, 2026)
This community service activity aims to strengthen farmers’ capacity to develop an environmentally friendly integrated farming system based on organic rice-fish farming through a Focus Group Discussion approach grounded in global collaboration. The activity was conducted in Tanah Merah Village, Serdang Bedagai District, and involved farmer groups, the local government, academics, and international partners from Srinakharinwirot University, Thailand. The method used was a participatory approach through the stages of problem identification, guided group discussions, technology dissemination, and the formulation of recommendations. The activity results showed an increase in community understanding of the integration of rice and fish farming, as well as the importance of downstream product processing and standardization. The Focus Group Discussion also successfully identified key issues, including limited marketing opportunities, weak farmer institutions, and dependence on chemical inputs. Additionally, international collaboration contributed to the transfer of food production technology and the enhancement of product value.